2022
DOI: 10.1186/s12889-022-14517-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between depression symptoms and academic performance among first-year undergraduate students at a South African university: a cross-sectional study

Abstract: Background: South African universities face a challenge of low throughput rates, with most students failing to complete their studies within the minimum regulatory time. Literature has begun to investigate the contribution of well-being, including mental health, with depression among students being one of the most common mental disorders explored. However, locally relevant research exploring associations between depression and academic performance has been limited. This research hypothesizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The authors found that approximately 40% of fifth-year medical students face difficulties coping with academic demands. In line with this, previous reports identified study year as a factor contributing to depression ( Chen et al, 2018 ; Wagner et al, 2022 ), stress, anxiety ( Barakat et al, 2016 ), procrastination ( Ibrahim et al, 2021 ), and insomnia ( Roka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 76%
“…The authors found that approximately 40% of fifth-year medical students face difficulties coping with academic demands. In line with this, previous reports identified study year as a factor contributing to depression ( Chen et al, 2018 ; Wagner et al, 2022 ), stress, anxiety ( Barakat et al, 2016 ), procrastination ( Ibrahim et al, 2021 ), and insomnia ( Roka et al, 2020 ).…”
Section: Discussionsupporting
confidence: 76%
“…For instance, Seehuus et al (2021) found 13.67% prevalence of severe and extremely severe anxiety symptoms among American college students. Wagner et al (2022) reported 18% prevalence of severe anxiety symptoms, and Bantjes et al (2023) found 10.9% prevalence of recent (past 30 days) generalised anxiety disorder. Naylor (2022) observed 47.9% severe anxiety symptoms among students with low tertiary entrance scores, aligning closely with this study's findings.…”
Section: Discussionmentioning
confidence: 99%
“…Seehuus et al (2021) found 12.29% prevalence of severe and extremely severe depression symptoms in American college students using the DASS-21 questionnaire. Wagner et al (2022) reported a 10% prevalence of severe depression symptoms in first-year undergraduates at a South African university using the Patient Health Questionnaire-9. Bantjes et al (2023) found a 15.4% prevalence of recent major depressive episodes among undergraduate students at 17 South African public universities using the Composite International Diagnostic Interview Screening Scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression has become widespread among university students and is understood as a critical barrier to academic performance at the university ( Jiang et al, 2022 , Wagner et al, 2022 ). Systematic reviews show that the occurrence of depressive symptoms is higher among university students than among non-college students or the general population ( Akhtar et al, 2020 , Luo et al, 2021 , Zou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%